2015
DOI: 10.1089/pho.2015.3916
|View full text |Cite
|
Sign up to set email alerts
|

Red Light Modulates Ultraviolet-Induced Gene Expression in the Epidermis of Hairless Mice

Abstract: Objective: The purpose of this study was to investigate whether low-level light therapy (LLLT) was capable of modulating expression of ultraviolet (UV) light-responsive genes in vivo. Materials and methods: The effects of 670 nm light-emitting diode (LED) array irradiation were investigated in a hairless SHK-1 mouse epidermis model. Mice were given a single dose of UVA/UVB light, or three doses of red light (670 nm @ 8 mW/cm 2 x 312 sec, 2.5 J/cm 2 per session) spread over 24 h along with combinations of pre-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…reported that photodynamic therapy, using wavelengths of 613–645 nm, significantly induced the expression of the pro‐inflammatory cytokines, IL‐1β, TNF‐α and TGF‐β . Furthermore, in a recent study, expression of Fos, the key molecular component contributing to DNA damage after exposure to UV light, decreased after treatment with red light (670 nm) …”
Section: Discussionmentioning
confidence: 96%
“…reported that photodynamic therapy, using wavelengths of 613–645 nm, significantly induced the expression of the pro‐inflammatory cytokines, IL‐1β, TNF‐α and TGF‐β . Furthermore, in a recent study, expression of Fos, the key molecular component contributing to DNA damage after exposure to UV light, decreased after treatment with red light (670 nm) …”
Section: Discussionmentioning
confidence: 96%
“…Consequently, these species kill and destroy the unwanted cells and tissues being targeted. Meanwhile, PBM therapy is known for the induction of beneficial clinical effects such as reduction of pain and inflammation, stimulation of wound healing, and hair regrowth. The basic mechanism of PBM consists of exposure to red or near-infrared light, at specific irradiances and low doses, and subsequent absorption by endogenous cytochrome c oxidase, leading to a cascade of effects (illustrated in Figure a). We proved the capability of QLEDs as photomedical light sources by PDT and PBM in vitro testing and parallel comparison with the efficacy of commercial LEDs.…”
Section: In Vitro Photobiomodulation and Photodynamic Therapy Feasibi...mentioning
confidence: 99%
“…We believe that the methods of modern genomics will be sufficient for decoding the resonance code of DNA: genetic engineering with subsequent measurement of spectral properties and full-genome mapping of the influence of waves on the openness and transcription of DNA. Toward that goal, we have shown the effect of red light on the expression of candidate genes in the murine epidermis (Myakishev-Rempel et al, 2015).…”
Section: Frequenciesmentioning
confidence: 99%